Professional Development of Outstanding Physics Teachers - Liu , Tingting; Sun , Haibin (Professional Development of Outstanding Physics Teachers, 2023)
The professional development of teachers is the requirement and inevitable trend of the development of modern teacher education. Cultivating teachers with professional standards has become the core goal of teacher education. Many countries have paid great attention to education and have put tremendous effort into constructing the teaching staff. Excellent and outstanding teachers are the core element of quality education services, the exemplary representatives of talents in education and the mainstay of innovation-driven development in education. Excellent and outstanding teachers constantly strive to achieve social justice by creating equal opportunities for students from different backgrounds. This book reviewed the teacher professional development and teacher education policy in the world. The knowledge structure of physics teachers and physics teachers’ pedagogical content knowledge (PCK) are analyzed. Based on the questionnaire survey, the development status of physics teachers’ PCK, the professional development levels of excellent and outstanding physics teachers are obtained. Based on the above research, the training strategy of excellent pre-service physics teachers is further analyzed.